A proposed model for medical records managing using blockchain: an analytical study (Comprehensive Journal of Science, 2025)
Electronic medical records (EMRs) represent a cornerstone of modern healthcare systems; however, challenges such as data fragmentation in paper and electronic formats, inefficient management, limited accessibility, and security and privacy concerns remain significant obstacles to building an integrated health system. This paper proposes a blockchain-based model, specifically utilizing Hyperledger Fabric, to aggregate patients’ medical records from multiple sources within a unified and secure framework. The proposed model leverages blockchain features—transparency, decentralization, and immutability—while granting patients full control over access permissions through a direct consent mechanism implemented via smart contracts and digital signatures. Physicians can request access to a patient’s data, which the patient may approve or reject, while laboratory results are shared through private channels to preserve confidentiality and ensure regulatory compliance. The system defines distinct roles for hospitals, insurance companies, and the Ministry of Health in administrative and financial processes without granting direct access to medical records. A prototype experiment demonstrated the efficiency of the model in enhancing data protection and achieving transparency, paving the way for broader practical applications. The paper also highlights challenges related to system performance, integration with existing infrastructures, and legal considerations, while outlining the expected impact on improving healthcare quality and enabling secure, real-time access to patients’ medical histories.
Keywords: Electronic Medical Records (EMRs) ,Hyperledger Fabric ,Smart Contracts ,Healthcare Data Privacy , Access Control Management ,Digital Healthcare